Pengaruh BI Rate, Kredit Perbankan, dan Pertumbuhan Ekonomi terhadap Stabilitas Sistem Keuangan di Indonesia pada Periode 2015–2025 - Safira Azzahra; Herlitah Herlitah; Saparuddin Mukhtar (Indo Publishing, 2026)
This study aims to analyze the effect of BI Rate, bank credit, and economic growth on the Financial System Stability Index (FSSI) in Indonesia during the 2015–2025 period. The research uses a quantitative approach with multiple linear regression analysis using the Ordinary Least Squares (OLS) method on time series data. The results show that the BI Rate has a positive but not significant effect on FSSI (probability 0.3804 > 0.05), indicating that changes in the policy interest rate do not directly determine financial system stability due to the monetary transmission lag. Bank credit has a negative and significant effect on FSSI (probability 0.0002 < 0.05), reflecting that credit distribution during the research period still functions as a driver of financial intermediation that supports economic activity, thereby reducing pressure on the financial system. Economic growth has a positive but not significant effect on FSSI (probability 0.8064 > 0.05), suggesting that economic growth has not been a primary factor explaining changes in financial system stability. Simultaneously, BI Rate, bank credit, and economic growth significantly affect FSSI (F-statistic 6.263185; probability 0.001377). The R² value of 0.319607 indicates that these three variables explain 31.96% of FSSI variations, while the remaining 68.04% is influenced by other factors outside the model, such as inflation, exchange rates, credit risk, liquidity, and global economic pressures.